Basic and other measurements of radiation at station Syowa (1994-01 et seq) - Junji Hisamitsu; Osamu Ijima; Yutaka Ogawa; Yoshinobu Tanaka; Hiroyuki Ogihara; Masato Fukuda; Koji Kawashima; Motohisa Doi; Takashi Yamanouchi (PANGAEA, 2023)
This is a compilation of all short-wave and long-wave radiation datasets from Syowa that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).